2021
DOI: 10.3390/plants10081595
|View full text |Cite
|
Sign up to set email alerts
|

Jute Responses and Tolerance to Abiotic Stress: Mechanisms and Approaches

Abstract: Jute (Corchorus spp.) belongs to the Malvaceae family, and there are two species of jute, C. capsularis and C. olitorious. It is the second-largest natural bast fiber in the world according to production, which has diverse uses not only as a fiber but also as multiple industrial materials. Because of climate change, plants experience various stressors such as salt, drought, heat, cold, metal/metalloid toxicity, and flooding. Although jute is particularly adapted to grow in hot and humid climates, it is grown u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…In Arabidopsis, AtSnRK2.3 also showed its involvement in water stress response mainly in leaves [11]. It is evident that the C. capsularis is tolerated against waterlogging conditions, whereas C. oiltorius is susceptible in water stress [87] and CcSnRK2.4b expression is higher over the period of time but CoSnRK2.4b expression reduce over the period of time. Again, abiotic stress (salinity and drought) transcriptome data revealed that SnRK2.3, SnRK2.7, and SnRK2.8 in both Corchorus species are upregulated in drought conditions.…”
Section: Jute Snrk2 Genes Are Involved In Abiotic Stress Resistancementioning
confidence: 99%
“…In Arabidopsis, AtSnRK2.3 also showed its involvement in water stress response mainly in leaves [11]. It is evident that the C. capsularis is tolerated against waterlogging conditions, whereas C. oiltorius is susceptible in water stress [87] and CcSnRK2.4b expression is higher over the period of time but CoSnRK2.4b expression reduce over the period of time. Again, abiotic stress (salinity and drought) transcriptome data revealed that SnRK2.3, SnRK2.7, and SnRK2.8 in both Corchorus species are upregulated in drought conditions.…”
Section: Jute Snrk2 Genes Are Involved In Abiotic Stress Resistancementioning
confidence: 99%
“…One plant that is adversely affected by salt stress is jute ( Corchorus olitorius L.), a crop plant that is widely cultivated on the Asian and African continents for its bast fibers, which are used in a wide range of marketable products [ 21 ]. However, environmental stresses, such as salt stress, adversely affect both the quantity of the fibers produced by the plant and the fiber quality, as well as jute germination, growth, and physiology [ 22 , 23 ]. The aim of the present study was to investigate the effects of soil supplementation with BC and CHT, focusing on the mediation of ROS-induced damage due to salt stress by stimulation of the antioxidative and glyoxalase pathways in jute plants.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Gomes et al (2011) found that increasing Na+ decreased cytosolic K + levels. Na + also causes plants to increase cytosolic Ca 2+ in response (Munns and Tester 2008 Rahman et al 2021). Furthermore, salinity has been found to impact plant development through Mg 2+ deficit (Khan et al 2000), which is consistent with our magnesium findings for M. parviflora and R. dentatus.…”
Section: Discussionmentioning
confidence: 99%